"Form fading among fading forms" death, language and madness in the novels of Samuel Beckett - Springer, Michael Leicester (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2008)
The primary thesis of this dissertation is that the development of narrative strategy and technique through the course of Samuel Beckett's fictional oeuvre enacts a parody of the Cartesian method of doubt, in which the search for first principles, instead of providing grounds for certainty, is a hopeless, grotesque quest for a self which eludes any and every assertion. My chief concerns are thus, firstly, to explicate and elucidate the nature of such narrative strategies and techniques, and how these can be said to parody epistemological procedure; and secondly, to interrogate the implications of this parody for the epistemological and interpretative endeavour of which the human sciences are comprised. These two issues are explored by way of an examination of Beckett's earliest novel, Murphy, and the narrative impasse that arises from the contradiction between this work's largely realist form and quasi-postmodern content. I thereafter argue that the later fiction, most particularly the Trilogy, achieves formal and stylistic solutions to the aesthetic and epistemological challenges raised by the earlier work. Beckett's fictional oeuvre, I contend, can best be construed as an attempt to attain that which exceeds and escapes narrative in and through narrative, namely madness or death. The achievement of either would entail the obliteration of the possibility of narrating at all, and the novels, engaging in a self-deconstructing endeavour, thus occupy a profoundly paradoxical position. Any attempt to interpret a body of work of this nature can only respond in an analogous manner, by trying to make meaning of the subversion of meaning, and deconstructing the assumptions that inform its procedures. This dissertation argues that it is precisely in the way in which it necessitates such selfreflexive discursive analysis that the import of Samuel Beckett's fiction lies, and extrapolates the significance of this for an understanding of discourse, literary criticism, and epistemological procedure.
Keywords: Beckett, Samuel, 1906-1989 -- Criticism and interpretation; English fiction -- 20th century -- History and criticism; Death in literature; Mental illness in literature